Radioactive Beams for Image-Guided Particle Therapy: The BARB Experiment at GSI - Boscolo, Daria; Kostyleva, Daria; Safari, Mohammad Javad; Anagnostatou, Vasiliki; Äystö, Juha; Bagchi, Soumya; Binder, Tim; Dedes, Georgios; Dendooven, Peter; Dickel, Timo; Drozd, Vasyl; Franczack, Bernhard; et al. (Frontiers in Oncology, 2021)
Several techniques are under development for image-guidance in particle therapy. Positron emission tomography (PET) is in use since many years, because accelerated charged particles generate positron-emitting isotopes by nuclear fragmentation in the human body. In heavy ion therapy, most of the PET signal is generated by projectile fragments. A much higher number of coincidences could be counted using radioactive (beta+-decay) beams directly for treatment. This idea has always been hampered by the low intensity of the secondary beams, produced by fragmentation of the primary, stable beams. With the intensity upgrade of the SIS-18 synchrotron in the FAIR-phase-0 in Darmstadt, it is now possible to reach radioactive ion beams sufficiently intense to treat a tumor in small animals. This was the motivation of the BARB (Biomedical Applications of Radioactive ion Beams) experiment that is ongoing at GSI in Darmstadt. This paper will present the plans and instruments developed by the BARB collaboration for testing the use of radioactive beams in cancer therapy.